PENGARUH KUALITAS LAYANAN JASA DAN HARGA TERHADAP KEPUASAN PELANGGAN PT. BUKITAPIT BUMI PERSADA - Melya Fitriyana; Donny Dharmawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
Bukitapit Bumi Persada is one of the first local companies in the field of oil and gas industry services in Indonesia. One of the advantages is, 100% percent locally owned and utilization of local resources, so that PT. Buktapit Bumi Persada is able to compete with other foreign companies. PT. Bukitapit Bumi Perasada currently serves not only local oil companies (Pertamina), but also has completed several projects with other oil companies. This study aims to analyze the effect of service quality and price policy on customer satisfaction at PT Bukitapit Bumi Persada. The population and sample of the research were 31 clients and the technique used in the research was non probability sampling with saturated sampling. The results showed that service quality and pricing policies affect customer satisfaction PT. Perasada Earth Bukitapit.